DUPLICITY AND EVOLUTION STATUS OF THE EARLY-TYPE Be STAR V622Per, THE MEMBER OF THE χ Per OPEN STAR CLUSTER - Malchenko, S. L.; Tarasov, A. E.; Yakut, K. (Одеські астрономічні публікації, 2007)
On high-resolution spectra, obtained in the Hα region and medium resolution spectra obtained in the region 4420-4960A together with radial velocities, which was taken from other published sources we analyzed the radial velocities and calculate orbital parameters of the massive binary system V622 Per. It is shown that the system has an orbital period 5.2 days and is a post mass transfer binary. Temperature of components and an inclination angle of the system were obtained from light curve analysis of the ellipsoidal variability. Luminosity ration of components was found of about 4:1. Teff and log g for each of components was estimated. It is shown that primary, less massive but brighter star is an evolved object that has lost a large part of the mass during its evolution. Estimations of the primary chemical composition showed a noticeable enrichment of products of the CNO cycles such as He/H reach 0.18, the nitrogen is in excess of about 0.5 dex, the carbon has lower abundances (by 2-3 dex lower) and the oxygen has 1 dex lower than solar abundance. The possible evolution of the binary with the known age 17 Myear is discussed.